2022
DOI: 10.3389/fnut.2022.1005181
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, purification, structure, modification, and biological activity of traditional Chinese medicine polysaccharides: A review

Abstract: Traditional Chinese medicines (TCM), as the unique natural resource, are rich in polysaccharides, polyphenols, proteins, amino acid, fats, vitamins, and other components. Hence, TCM have high medical and nutritional values. Polysaccharides are one of the most important active components in TCM. Growing reports have indicated that TCM polysaccharides (TCMPs) have various biological activities, such as antioxidant, anti-aging, immunomodulatory, hypoglycemic, hypolipidemic, anti-tumor, anti-inflammatory, and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 139 publications
0
10
0
Order By: Relevance
“…Traditional Chinese medicine (TCM) is another field where researchers have tested compounds for their effects on longevity and healthspan ( Zhao and Luo, 2017 ) ( Table 5 ). TCM has a long history, and many herbs and their components are being studied now in a variety of diseases where they show beneficial effects, including aging ( Chen et al, 2019 ; Bi et al, 2022 ; Xue et al, 2022 ). The flavanol Icariin, an ingredient of the herb Epimedium , improved the median lifespan in male mice by 8%, accompanied by improved muscle function and coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Traditional Chinese medicine (TCM) is another field where researchers have tested compounds for their effects on longevity and healthspan ( Zhao and Luo, 2017 ) ( Table 5 ). TCM has a long history, and many herbs and their components are being studied now in a variety of diseases where they show beneficial effects, including aging ( Chen et al, 2019 ; Bi et al, 2022 ; Xue et al, 2022 ). The flavanol Icariin, an ingredient of the herb Epimedium , improved the median lifespan in male mice by 8%, accompanied by improved muscle function and coordination.…”
Section: Resultsmentioning
confidence: 99%
“…AAP I, AAP II and AAP III was obtained by anion-exchange methods [ 20 ]. Crude polysaccharides of Auricularia auricula were prepared into 2 mg (Glucose equivalent)/mL solution and purified by anion-exchange chromatography (DEAE-52-cellulose chromatography column, 2.5 cm i.d.…”
Section: Methodsmentioning
confidence: 99%
“…The yields of polysaccharides from biphasic aqueous extraction are larger than those from regular aqueous extraction, yet the challenge remains in precisely and swiftly determining the appropriate biphasic solution. 12 While there are benefits and drawbacks to each extraction technique, plant polysaccharides are still mostly extracted via water extraction, diluted alkaline extraction, and other techniques because of equipment constraints and expense. Numerous factors can impact the polysaccharide extraction efficiency.…”
Section: The Extraction Of Mulberry Polysaccharidesmentioning
confidence: 99%
“…Structural modification can enhance the polysaccharide's biological action by changing the molecular structure, molecular weight, quantity, and location of polysaccharide substituent groups and even obtaining new biologically active polysaccharide derivatives. 12 Current methods for obtaining polysaccharide derivatives include sulfation, carboxymethylation, acetylation, alkylation modifications, and so on. Chen found that selenated mulberry polysaccharides showed a higher scavenging capacity of peroxyl radicals in vitro than selenated mulberry polysaccharides, could lower blood glucose by promoting insulin secretion and pancreatic cell proliferation, and had a more significant hypoglycemic effect than unselenated mulberry polysaccharides.…”
Section: Structural Modification Of Mulberry Polysaccharidesmentioning
confidence: 99%